2017
DOI: 10.1002/jor.23658
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound elastography for carpal tunnel pressure measurement: A cadaveric validation study

Abstract: Carpal tunnel pressure is a key factor in the etiology of carpal tunnel syndrome. Numerous approaches have been conducted to measure carpal tunnel pressure. However, most techniques are invasive and take time and effort. We have developed an innovative approach to noninvasively assess the tunnel pressure by using the ultrasound surface wave elastography (USWE) technique. In a previous study it was shown that the shear wave speed in a tendon increased linearly with increasing tunnel pressure enclosed the tendon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…C, Demonstrates increased median nerve stiffness in mild carpal tunnel syndrome, which is further increased in severe carpal tunnel syndrome (D). D, Note that in severe carpal tunnel syndrome there is an increase in the stiffness of all of the contents of the carpal tunnel, which correlates with increasing carpal tunnel pressure 70 where G is shear modulus, ρ is tissue density (ffi1000 kg/m 3 ) and c is SWV. Tissue density will vary for different types of soft tissues.…”
mentioning
confidence: 99%
“…C, Demonstrates increased median nerve stiffness in mild carpal tunnel syndrome, which is further increased in severe carpal tunnel syndrome (D). D, Note that in severe carpal tunnel syndrome there is an increase in the stiffness of all of the contents of the carpal tunnel, which correlates with increasing carpal tunnel pressure 70 where G is shear modulus, ρ is tissue density (ffi1000 kg/m 3 ) and c is SWV. Tissue density will vary for different types of soft tissues.…”
mentioning
confidence: 99%
“…Previous publications have described the potential of elastography for CTS, with the majority reporting increased nerve stiffness (ratios) in patients with CTS 20–32 ; three research studies reported no significant difference 33–35 . In addition, US elastography has been used to assess carpal ligament stiffness, 36,37 intra carpal tunnel pressure, 38,39 the correlation between median nerve area and strain 40 and the difference in median nerve elasticity before and after carpal tunnel release 41 . These studies support the notion that the nerve's mechanical properties change in CTS patients, but the majority used strain elastography with manual compression to induce the tissue strain.…”
Section: Introductionmentioning
confidence: 73%
“…The softening of the traction-separation relationship is attributed to the softening behavior of the medial interfacial strength, plaque, or fibrous cap [28][29][30]. Hence, these CZMs are able to characterize the mechanical response of the cohesive element during the crack propagation.…”
Section: Effects and Features Of Four Shapes Of Czms In Simulating Thmentioning
confidence: 99%